Effect of Au film mask on antiwetting and antireflection properties of nanostructural polymer by plasma nanotexturing. (1st September 2022) - Li, Xiao-Yu; Li, Yu-Peng; Huo, Lei; Lei, Ming-Kai
Abstract: Capacitively coupled radiofrequency plasma nanotexturing assisted by an Au film mask is carried out to fabricate the fluorocarbon-film decorated nanowires bundles from the semicrystalline polyethylene (PE) and amorphous PolyMethyl methacrylate (PMMA) subatrates. The spacing distance and height of the nanowires in a bundle on the PE and PMMA substrates are adjusted by the thickness of Au film mask. The complete rebound phenomenon occurs when the droplets impact with a high speed on the nanowire bundles. The nanowire bundles exhibit an improved superhydrophobicity. The narrow spacing distance between the nanowires is beneficial to the antiwetting of superhydrophobic surface. The low reflectivity of the nanowire bundles is also obtained with an incident light wavelength from 400 to 2000 nm. The antireflection property of the nanowire bundles is caused by the high height of nanowires in a bundle. The nanowire bundles on the PE and PMMA substrates prepared by the plasma nanotexturing assisted by the Au film mask have the excellent antiwetting and antireflection properties.